2016
DOI: 10.5812/hepatmon.34219
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Hepatitis A Virus Epidemiology in Nursing Students and Adherence to Preventive Measures at Two Training Wards of a University Hospital

Abstract: BackgroundNursing students can be exposed to patients with hepatitis A virus (HAV) and can represent a vehicle of transmission both for health personnel, patients and relatives.ObjectivesThe aim of this study was to assess the risk of HAV infection in nursing students during their internship.Patients and MethodsA seroprevalence survey on HAV infection was performed on nursing students at the Cagliari university-hospital, together with the assessment of the compliance to preventive measures to decrease the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…In this study, using a univariate analysis (chi-square test), it was determined that anti-HAV seropositivity was significantly higher among male students than among female students. This result was not in agreement with the observations reported in other studies [12,14,16,19]. We have no explanation for this finding.…”
Section: Sexcontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, using a univariate analysis (chi-square test), it was determined that anti-HAV seropositivity was significantly higher among male students than among female students. This result was not in agreement with the observations reported in other studies [12,14,16,19]. We have no explanation for this finding.…”
Section: Sexcontrasting
confidence: 99%
“…In Korea, anti-HAV seropositivity was reported as 11.4% among 1st-to 3rd-year medical school students [13], and in medical students in Iran, the prevalence of anti-HAV seropositivity was 70% in one study [14] and 34% in another study [15]. In another study from Italy, 3.16% of nursing students were immune to the HAV [16]. These differences between studies may be attributed to the health behaviors of participants, hygiene, sanitary conditions, and socioeconomic levels of the country.…”
Section: Sexmentioning
confidence: 99%
“…Especially in the emergency intensive care unit (EICU), patients usually tend to be older with more comorbidities and lower immunity, and there are more multidrug-resistant pathogens, more invasive diagnosis and treatment operations, and more antibiotic applications, all of which lead to the higher incidence of hospital infection [4]. Although there is sufficient evidence that compliance with hand hygiene can reduce the incidence of nosocomial infections and cross-infection of drug-resistant bacteria, hand hygiene habits in developed and developing countries have been shown to be inadequate [5]. Hand hygiene definitely needs more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in spite of CDC guidelines that recognize HH as the most significant process in the prevention of nosocomial infection,[ 9 ] an unacceptable compliance rate is still observed among health-care professionals (HCPs). [ 10 ] Nigeria is one of the countries with a high burden of HCAIs,[ 11 12 ] yet the HH campaign is not commonly promoted in many health-care facilities in the country. Some researchers have shown that adherence of HCPs to guidelines for HH is very low, generally <50%.…”
Section: Introductionmentioning
confidence: 99%